Tinjauan Hukum Terhadap Perlindungan Hak Pemilik Kendaraan dalam Kasus Penggelapan oleh Penyewa - Hendra Dwi Kurnia; Retno Dewi Pulung Sari (Jurnal Hukum Caraka Justitia, 2026)
The increasing incidence of vehicle embezzlement in Indonesia, particularly in rental car businesses, highlights legal gaps in protecting owners against misuse by renters. This study aims to examine the legal framework and available protection mechanisms for vehicle owners when renters commit embezzlement after legally acquiring vehicles through rental agreements. Using a normative juridical method with statutory and conceptual approaches, the research analyzes provisions under Indonesian criminal law (KUHP), civil law (KUHPerdata), and procedural law (KUHAP). The findings indicate that such cases fulfill the elements of embezzlement as defined in Article 372 of the Criminal Code and often overlap with civil breaches, such as default or unlawful acts. It was also found that weak contract structures and the lack of clear legal clauses make law enforcement and recovery of losses more difficult. The study emphasizes that written agreements, with explicit terms and legal sanctions, are crucial to strengthen the owner's legal position. The implication of this research is the need for preventive legal awareness and stronger contractual practices among vehicle owners, as well as coordinated law enforcement responses to ensure justice and legal certainty in rental-related embezzlement cases.